A gain or a loss? The consequences of Brexit in the opinions of Polish migrants - Stanisław Fel; Marek Wódka; Jarosław Kozak (Comparative Economic Research. Central and Eastern Europe, 2022)
The aim of the article is to present the opinions of Polish migrants in Britain on the gains or losses that Brexit may bring to the European Union (EU), the United Kingdom (UK), and Poland, as well as the respondents themselves and their families. These opinions were determined based on the analysis of the results of a survey carried out among these migrants and presented against the backdrop of the results of public opinion polls on EU membership, which have been conducted in the British Isles regularly since the 1970s. The article analyses the beliefs held on this issue by economic migrants, who are faced with a choice as Brexit is underway: to remain expatriates or to return to their country of origin. Among the answers to questions about the possible benefits or negative outcomes of Brexit, it was the latter that predominated. In the discussion, the authors seek to ascertain why migrants from Poland fear the negative consequences of Brexit for the UK and for Europe more often than they fear those for Poland or for themselves and their close family members.
Keywords: F22; F55; O15; O24; O52; Z19; 330; Brexit; migrants; public opinion; Brexit's gains and losses